Dental radiographic superimposition: An exciting addition to the forensic odontology armamentarium. (September 2022) - Robinson, Liam; Smit, Chané; Bernitz, Herman
Highlights: Forensic odontology plays an important role in the identification of severely decomposed or carbonised corpses. Forensic odontologists were consulted for the identification of a severely carbonised corpse with extensive dental restorative work. Superimposition of ante- and post-mortem dental radiographs were utilised in the positive identification process. Abstract: Forensic odontology plays an important role in the identification of severely decomposed or carbonised corpses, particularly when conventional identification methods fail. This case report highlights the use of dental radiographic superimposition of extensive dental restorative work in the identification of a severely carbonised corpse. Ante- and post-mortem radiographs were analysed via superimposition using the Adobe Photoshop® 2021 image manipulation software. Multiple concordant features, as well as near-perfect radiographic superimposition, enabled a positive identification of the carbonised corpse. This emphasises the need for consultation of forensic odontologists in cases where dental restorative work is noted during post-mortem examination.